(untitled) (Al-Academy, 2025)
The historical landmarks and symbols in the land of Mesopotamia, which is rich in numerous monuments that still stand to this day, are considered important sources. There is a vast diversity in the symbols, their classifications, and their various fields, which illustrate the richness of life among the ancient Iraqis. This also indicates the skill and diverse abilities of the ancient Iraqis, and their ability to discover and make use of their surroundings in service of the Iraqi civilization. The ancient Iraqis recorded their daily lives on the walls of temples and cave ceilings through sculptures and drawings, which have been discovered by archaeologists and researchers. Thus, historical symbolic meanings are derived through analyzing mental representations, highlighting significance according to the designer’s imagination and capabilities to convey ideas in contemporary designs. Therefore, the research problem is defined by the following question: What are the most important symbols used in the design of tourism advertisements for the Iraqi Tourism and Antiquities Authority?